Respuesta :
Answer:
-3, 9
Step-by-step explanation:
x^2 -6x - 27=
= x^2 - 9x + 3x - 27
= x(x - 9) + 3(x - 9)
= (x + 3)(x - 9)
x = -3, x = 9
Answer:
x = 9
x = - 3
Step-by-step explanation:
This factors.
The best way to do this is to start by seeing what answers are possible. Start with 27. What 2 numbers multiply to 27. There aren't many.
27: 1 * 27
27: 3*9
Now you need the two numbers to add to -6. That means the larger one should be -
The answer is 3 and 9
So the factors are
(x - 9)(x + 3)
x - 9 = 0
x = 9
========
x + 3 = 0
x = - 3
================
The intercepts are the points (9,0) and (-3,0)
x = 9
x = - 3